PENGARUH MODEL PROBLEM LEARNING DENGAN PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 4 PALU - Manap Trianto; Yulia Windarsih; Anisa Anisa (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2021)
This study aims to determine whether there is an effect of the Problem Based Learning learning model with a scientific approach on the learning outcomes of class X students of SMA Negeri 4 Palu. The success of this research is seen from the results of the final exam or posttest in the experimental class using the Problem Based Learning model with a scientific approach. This type of research uses pre experimental designs with one group pretest-posttest design. The population of this study were all students of class X SMA Negeri 4 Palu (X IPA 5). The sampling technique is purposive sampling. The average percentage of pretest learning outcomes is 52.13 and the posttest average percentage is 73.02. Analysis of hypothesis testing data using t-test with a significance value of 0.05. obtained a thiting value = 12.802 > t table = 1.66980 with a significance value of p < 0.05. It can be concluded that H1 is accepted and H0 is rejected, which means that there is an increase in student learning outcomes using the Problem Based Learning learning model with a scientific approach.